Projections of Cargo Transport by Air and Number of Fleets on Economic Growth at Soekarno Hatta Airport - Oce Prasetya; Shakira Anisa Maharani; Sylvia Sayyidatul Fitria Afrenda Novianti; Suharto Abdul Majid (Green Publisher, 2025)
Air cargo is one of the important sectors in the national economy, because it can support the mobility of goods and services between regions and countries. Soekarno Hatta Airport as the largest and busiest airport in Indonesia, has a strategic role in domestic air cargo services. This study aims to analyze the projection of cargo transportation by air and the number of fleets on the regional economic growth of Banten province at Soekarno Hatta Airport. The method used is a quantitative descriptive research method, by describing natural phenomena that occur during research and using secondary data / indirect data and conducting group discussions to obtain joint decisions. The data used include 2022 air transport data and 2022 Banten provincial report data. The results of forecasting the amount of cargo demand at Soekarno Hatta International Airport for the next 5 years in 2027 amounted to 386,957,736 Kg. The results of forecasting the number of fleets at Soekarno Hatta International Airport for the next 5 years in 2027 amounted to 12,063 fleets. The results of forecasting economic growth in Banten Province for the next 5 years in 2027 amounted to 2.03%. The air transportation and air cargo sector can be the most influential factor in the economic growth of Banten Province if there is cooperation to support the work programs of each institution.